Ways to unravel the clinical potential of carbon ions for head and neck cancer reirradiation: dosimetric comparison and local failure pattern analysis as part of the prospective randomized CARE trial - Held, Thomas; Tessonnier, Thomas; Franke, Henrik; Regnery, Sebastian; Bauer, Lukas; Kozyra, Katharina; Harrabi, Semi B.; Herfarth, Klaus; Mairani, Andrea; Debus, Jürgen; Adeberg, Sebastian (Radiation oncology, 2022)
BACKGROUND: Carbon ion radiotherapy (CIRT) yields biophysical advantages compared to photons but randomized studies for the reirradiation setting are pending. The aim of the current project was to evaluate potential clinical benefits and drawbacks of CIRT compared to volumetric modulated arc therapy (VMAT) in recurrent head and neck cancer. - METHODS: Dose-volume parameters and local failure patterns of CIRT compared to VMAT were evaluate in 16 patients from the randomized CARE trial on head and neck cancer reirradiation. - RESULTS: Despite an increased target dose, CIRT resulted in significantly reduced organ at risk (OAR) dose across all patients (- 8.7% Dmean). The dose-volume benefits were most pronounced in the brainstem (- 20.7% Dmax) and the optic chiasma (- 13.0% Dmax). The most frequent local failure was type E (extraneous; 50%), followed type B (peripheral; 33%) and type A (central; 17%). In one patient with type A biological and/or dosimetric failure after CIRT, mMKM dose recalculation revealed reduced target coverage. - CONCLUSIONS: CIRT resulted in highly improved critical OAR sparing compared to VMAT across all head and neck cancer reirradiation scenarios despite an increased prescription dose. Local failure pattern analysis revealed further potential CIRT specific clinical benefits and potential pitfalls with regard to image-guidance and biological dose-optimization.
Gesehen am 11.08.2022